2020
DOI: 10.3390/jfb11020039
|View full text |Cite
|
Sign up to set email alerts
|

A 2,5-Dihydroxybenzoic Acid–Gelatin Conjugate Inhibits the Basal and Hsp90-Stimulated Migration and Invasion of Tumor Cells

Abstract: The extracellular cell surface-associated and soluble heat shock protein 90 (Hsp90) is known to participate in the migration and invasion of tumor cells. Earlier, we demonstrated that plasma membrane-associated heparan sulfate proteoglycans (HSPGs) bind the extracellular Hsp90 and thereby promote the Hsp90-mediated motility of tumor cells. Here, we showed that a conjugate of 2,5-dihydroxybenzoic acid with gelatin (2,5-DHBA–gelatin), a synthetic polymer with heparin-like properties, suppressed the basal (unstim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 51 publications
(155 reference statements)
0
1
0
Order By: Relevance
“…It can promote tumor progression by promoting cell invasion and metastasis and inhibiting apoptosis. 4,[9][10][11] By comparing the expression levels of HSP90α in the serum of healthy individuals and patients with lung cancer, Wang et al 12 found that the expression level of HSP90α in the serum of patients with lung cancer was higher than that of healthy individuals, suggesting that HSP90α can be used as a new biomarker for the diagnosis of lung cancer. Zhou et al 13 found that HSP90α in serum is consistent with tumor markers, such as carcinoembryonic antigen (CEA), and has a high diagnostic effect on patients with NSCLC.…”
Section: Introductionmentioning
confidence: 99%
“…It can promote tumor progression by promoting cell invasion and metastasis and inhibiting apoptosis. 4,[9][10][11] By comparing the expression levels of HSP90α in the serum of healthy individuals and patients with lung cancer, Wang et al 12 found that the expression level of HSP90α in the serum of patients with lung cancer was higher than that of healthy individuals, suggesting that HSP90α can be used as a new biomarker for the diagnosis of lung cancer. Zhou et al 13 found that HSP90α in serum is consistent with tumor markers, such as carcinoembryonic antigen (CEA), and has a high diagnostic effect on patients with NSCLC.…”
Section: Introductionmentioning
confidence: 99%